On a class of nonstationary curves in Hilbert spaces - Boeva, Anna (International Scientific Unity, 2024)
The paper discusses the cases of nonstationary random processes, the operator of which has one-dimensional imaginary component.
Keywords: stationary random processes; correlation; curves in Hilbert space; complex-valued process; correlation function